2004
DOI: 10.1002/j.0022-0337.2004.68.8.tb03836.x
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence Study of a Dental Anatomy Computer‐Assisted Learning Program

Abstract: Tooth Morphology is a computer-assisted learning program designed to teach the anatomy of the adult dentition. The purpose of this study was to test whether Tooth Morphology could teach dental anatomy to first-year dental students as well as the traditional lecture. A randomized controlled trial was performed with forty-five first-year dental students. The students were randomly assigned to either the Tooth Morphology group (n=23), which used the computer-assisted learning program and did not attend lecture, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 6 publications
1
59
0
9
Order By: Relevance
“…Studies have shown that these programs could replace traditional theoretical lectures in dental anatomy education. However, they do not replace the practice of dental carving (Bogacki et al, ; de Azevedo Rde et al, ). Haptic simulators such as MOOG Simodont ® Virtual Dental Trainer (Moog Inc., East Aurora, NY) have been successfully used in medical education but are relatively new.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that these programs could replace traditional theoretical lectures in dental anatomy education. However, they do not replace the practice of dental carving (Bogacki et al, ; de Azevedo Rde et al, ). Haptic simulators such as MOOG Simodont ® Virtual Dental Trainer (Moog Inc., East Aurora, NY) have been successfully used in medical education but are relatively new.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that dental schools also use dissection and prosection as a method of teaching gross anatomy (Snelling et al, ) as well as using specific dental C.A.L programs (Bogacki et al, ). There are also reports that highlight the use of models and didactic teaching methods for teaching gross anatomy to dental students (Obrez et al, ) and also the use of radiological methods (Berry and Ashman, ).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The use of computer assisted instruction along with traditional wax carving have also been suggested to enhance the learning capacity. 17,18 The main advantage of the computer assisted method was the possibility to repeat the technique again and again when needed. 16,17 Analysis of tooth is primary method used in human identifi cation especially in mass disaster and crime site investigation.…”
Section: Discussionmentioning
confidence: 99%